An accurate and stable alternating directional moving particle semi-implicit method for incompressible flow simulation - Date Li; Huaixin Zhang; Huilan Yao (Advances in Mechanical Engineering, 2022)
As a Lagrangian mesh free method, Moving Particle Semi-implicit (MPS) method can easily handle complex incompressible flow with free surface. However, some deficiencies of MPS method such as inaccurate results, unphysical pressure oscillation and particle thrust near free surface still required to be further resolved. In this paper, an improved MPS method based on Crank-Nicolson time scheme, named Alternating Direction Moving Particle Semi-implicit (ADMPS) method, is proposed. In addition, a time integral source term (TIS) is developed to suppress unphysical pressure oscillation and a free-surface revise (FR) technique is proposed to avoid particle thrust near free surface. Enhancement of accuracy and stability by these improvements is proved by hydrostatic and dam breaking benchmarks, and the numerical results of the ADMPS-FR-TIS model show good agreement with the hydrostatic analytical solution and the dam breaking experiment data.